Brachial Blood Pressure Invasively and Non-Invasively Obtained Using Oscillometry and Applanation Tonometry: Impact of Mean Blood Pressure Equations and Calibration Schemes on Agreement Levels - Bia, Daniel (2023)
The use of oscillometric methods to determine brachial blood pressure (bBP) can lead to a systematic underestimation of the invasively measured systolic (bSBP) and pulse (bPP) pressure levels, together with a significant overestimation of diastolic pressure (bDBP). Similarly, the agreement between brachial mean blood pressure (bMBP), invasively and non-invasively measured, can be affected by inaccurate estimations/assumptions. Despite several methodologies that can be applied to estimate bMBP non-invasively, there is no consensus on which approach leads to the most accurate estimation. Aims: to evaluate the association and agreement between: (1) non-invasive (oscillometry) and invasive bBP; (2) invasive bMBP, and bMBP (i) measured by oscillometry and (ii) calculated using six different equations; and (3) bSBP and bPP invasively and non-invasively obtained by applanation tonometry and employing different calibration methods. To this end, invasive aortic blood pressure and bBP (catheterization), and non-invasive bBP (oscillometry [Mobil-O-Graph] and brachial artery applanation tonometry [SphygmoCor]) were simultaneously obtained (34 subjects, 193 records). bMBP was calculated using different approaches. Results: (i) the agreement between invasive bBP and their respective non-invasive measurements (oscillometry) showed dependence on bBP levels (proportional error); (ii) among the different approaches used to obtain bMBP, the equation that includes a form factor equal to 33% (bMBP = bDBP + bPP/3) showed the best association with the invasive bMBP; (iii) the best approach to estimate invasive bSBP and bPP from tonometry recordings is based on the calibration scheme that employs oscillometric bMBP. On the contrary, the worst association between invasive and applanation tonometry-derived bBP levels was observed when the brachial pulse waveform was calibrated to bMBP quantified as bMBP = bDBP + bPP/3. Our study strongly emphasizes the need for methodological transparency and consensus for non-invasive bMBP assessment.